A biocompatible silicon nitride dental implant material prepared by digital light processing technology. (May 2023) - Zou, Rongfang; Bi, Lunan; Huang, Yang; Wang, Yadi; Wang, Yan; Li, Lin; Liu, Jiayin; Feng, Lu; Jiang, Xiaoxia; Deng, Bin
Abstract: For decades, titanium has been the preferred material for dental implant fabrication. However, metallic ions and particles can cause hypersensitivity and aseptic loosening. The growing demand for metal-free dental restorations has also promoted the development of ceramic-based dental implants, such as silicon nitride. In this study, silicon nitride (Si3 N4 ) dental implants were fabricated for biological engineering by photosensitive resin based digital light processing (DLP) technology, comparable to conventionally produced Si3 N4 ceramics. The flexural strength was (770 ± 35) MPa by the three-point bending method, and the fracture toughness was (13.3 ± 1.1) MPa · m 1/2 by the unilateral pre-cracked beam method. The elastic modulus measured by the bending method was (236 ± 10) GPa. To confirm whether the prepared Si3 N4 ceramics possessed good biocompatibility, in vitro biological experiments were performed with the fibroblast cell line L-929, and preferable cell proliferation and apoptosis were observed at the initial stages. Hemolysis test, oral mucous membrane irritation test, and acute systemic toxicity test (oral route) further confirmed that the Si3 N4 ceramics did not exhibit hemolysis reaction, oral mucosal stimulation, or systemic toxicity. The findings indicate that Si3 N4 dental implant restorations with personalized structures prepared by DLP technology have good mechanical properties and biocompatibility, which has great application potential in the future. Graphical abstract: Image 1